2015
DOI: 10.3390/publications3030155
|View full text |Cite
|
Sign up to set email alerts
|

Fee Waivers for Open Access Journals

Abstract: Abstract:Open access journals which charge article processing charges (APCs) sometimes offer fee waivers to authors who cannot afford to pay them. This article measures the extent of this practice among the largest toll access and open access publishers by gathering stated fee waiver policies from publishers' websites. A majority (68.8%) were found to offer fee waivers and sometimes they are only available to authors from low-and middle-income countries. This has implications for the ability of authors without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 17 publications
(21 reference statements)
0
29
0
2
Order By: Relevance
“…While many author‐pays journals adopt policies that reduce the financial barriers to publishing equitably (e.g., automatic waiver programs indexed to median research grant size in each country or automatic waivers for papers submitted from developing economies), a significant number have fixed charges (Lawson ). Some author‐pays journals offer reduced charges to people from developing economies, but even reduced charges are impossible for many potential authors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While many author‐pays journals adopt policies that reduce the financial barriers to publishing equitably (e.g., automatic waiver programs indexed to median research grant size in each country or automatic waivers for papers submitted from developing economies), a significant number have fixed charges (Lawson ). Some author‐pays journals offer reduced charges to people from developing economies, but even reduced charges are impossible for many potential authors.…”
mentioning
confidence: 99%
“…). It is harder for disadvantaged groups from these jurisdictions to appeal for waivers (Lawson ), deepening the divide between those who can pay and those who cannot.…”
mentioning
confidence: 99%
“…If researchers are committed to publishing in a particular journal (perhaps it is the flagship journal of our field, and we need tenure at a university whose administration focuses on impact factors), we can ask the journal to waive the cost, although it is unclear how often this is successful, and there is the potential for this to be an alienating process for researchers from under-resourced institutions, who may be hesitant to ask for waivers more than once and be judged for it. Lawson (2015) provided a review of fee waiver policies and found that 22 of the 32 publishers included in the review had an explicit fee waiver policy. Of those publishers with waiver policies, however, 36% reserved fee waivers for researchers from low-and middle-income countries.…”
Section: How To Engage In Open Access Publishing Practicesmentioning
confidence: 99%
“…[18] As academic journals, WikiJournals strive to follow recognised best practices in scholarly publishing, especially features advocated by the open access movement. [19][20] [21] In particular, we want to encourage open and collaborative reviews, [22] the use of preprints, [23] [24] and reviews based on scientific merit, rather than perceived novelty or importance. [25] In order to achieve this, 2.…”
Section: Wikijournalsmentioning
confidence: 99%